Frequency of Wound Infections in Patients Undergoing Caesarean Section - Faiza Sattar, Maryam Siddiqa, Asim Zahoor, Umer Zahoor, Ayesha Manzoor, Ali Zahoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of wound infections in patients undergoing elective and emergency caesarean section. Material and Methods: A total 140 patients with singleton or multiple pregnancy of cephalic presentation undergoing emergency or elective cesarean section were included Jan-2022 to April-2022. All this data (age, gestational age, parity (Primiparous/multiparous), previous history of cesarean section (yes/no), BMI, mode of cesarean (elective/emergency), duration of procedure, type of cesarean (conventional/lower segment) and wound infection (yes/no)) were recorded. Results: Mean age was 31.58±5.17 years. Mean gestational age of patients was 39.56±1.39 weeks. Mean duration of procedure of patients was 36.19±5.31 minutes. There were 64 (45.7%) patients having previous history of CS. Mode of cesarean section was elective in 107 (76.4%) and it was emergency in 33 (23.6%) patients. wound infections were found in 34 (20.24%) patients. Wound infections were found in 11 (33.3%) patients undergoing emergency CS and in 23 (17.0%) patients undergoing elective CS (p-value 0.037). Conclusion: In emergency CS, the rate of surgical site infections (SSIs) is greater than in elective CS. Therefore, in emergency situations, it is necessary to investigate the elements that lead to increased SSIs and to take care of them.